PENAMBAHAN GLUTE EXERCISE PADA TERAPI LATIHAN DASAR LEBIH MENINGKATKAN STABILITAS ANKLE PADA PENDERITA SPRAIN ANKLE KRONIS - Donal Syafrianto; Nyoman Mangku Karmaya; S. Indra Lesmana; Ida Bagus Ngurah; I Wayan Weta; Muh. Ali Imron (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Introduction: Chronic ankle sprain is an over stretch to the lateral ankle ligament complex on the motion inversion and plantar flexion. The weakness of the ligaments as a result of passive stability complaints of pain, chronic inflammation, impaired proprioceptive, until disorders of muscle activity ankle, knee and hip thus causing ankle instability. Chronic ankle sprain make ankle instability, which is accompanied by the reaction of the gluteus muscle strength decrease due to changes in muscle activation. Purpose: The purpose of this study was to prove whether the addition of glute exercise on the basis of exercise therapy further increase the stability of the ankle in case of chronic ankle sprain. Methods: The research method in this study is experimental design with pretest and posttest control group design. In this study, nine respondents were given basic training exercise therapy for 8 weeks with a frequency of exercise two times a week, and 9 respondents were given additional glute exercise therapy for 8 weeks of basic training exercise frequency 2 times a week. Measuring instrument used is the balance error scoring system (BESS). Results: Results of parametric statistical analysis with Paired sample t-test. Hypothesis test results show both treatment groups can significantly improve the stability of the ankle, before treatment in Group I with a mean of 23.67±5.408 and after treatment with a mean of 13.11 ± 3.887, and Prior Treatment in Group II 24.22 ± 4.024 and after treatment with a value of 8.89 ± 2.147 with p = 0.000 (p < 0.05). Different test by Independent sample t-test between the two groups was significant difference to the value of 10.56 ± 1.944 difference in Group I and Group II 15.22 ± 2.635 with p = 0.001 (p < 0.005). Conclusion: The conclusions of this research is the addition of glute exercise on the basis of exercise therapy further increase the stability of the ankle in patients with chronic ankle sprain.